2013
DOI: 10.1161/jaha.113.000304
|View full text |Cite
|
Sign up to set email alerts
|

Disease Location Is Associated With Survival in Patients With Peripheral Arterial Disease

Abstract: BackgroundWe investigated whether disease location influences survival in patients with peripheral arterial disease.Methods and ResultsPatients (n=12 731; mean age, 67.5±12.7 years; 57.4% male) who underwent outpatient noninvasive lower extremity arterial evaluation were followed up for 5.9±3.1 years for all‐cause mortality. Peripheral arterial disease (n=8930) was defined as a resting or postexercise ankle‐brachial index (ABI) ≤0.90, and normal ABI (n=3 801) was defined as a resting and postexercise ABI of 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
2
9

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(71 citation statements)
references
References 28 publications
(75 reference statements)
4
56
2
9
Order By: Relevance
“…Chen, et al demonstrated that patients with distal disease had a poorer prognosis than patients without distal disease, whereas patients with proximal disease showed no difference in prognosis. 17) Similarly, another study showed that multi-level disease was associated with a poorer prognosis in PAD patients. 16) Therefore, previous publications and our data showed that PAD lesion location affects the severity of CAD and prognosis in patients with lower extremity PAD.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Chen, et al demonstrated that patients with distal disease had a poorer prognosis than patients without distal disease, whereas patients with proximal disease showed no difference in prognosis. 17) Similarly, another study showed that multi-level disease was associated with a poorer prognosis in PAD patients. 16) Therefore, previous publications and our data showed that PAD lesion location affects the severity of CAD and prognosis in patients with lower extremity PAD.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies showed that the location of the lesion is associated with survival in patients with lower extremity PAD. 16,17) However, there are few studies on the relationship between PAD and CAD lesion location confirmed by angiography. We hypothesized that the location of the PAD lesion can predict the presence and severity of CAD.…”
Section: P Eripheral Artery Disease (Pad) Is Frequently Accompa-mentioning
confidence: 99%
“…This raises the question whether it is possible that the manifestation of atherosclerosis may present differentially among individual patients’ arteries. More aggressive expression of atherosclerosis has been found in patients with distal versus aortoiliac disease and in patients in whom higher inflammation markers can be found 17, 18, 19. These studies suggested which concomitant factors could be associated with a more aggressive underlying atherosclerotic process but were unable to document whether this could be linked to the number of lower extremity lesions and patient outcomes 17, 18.…”
Section: Discussionmentioning
confidence: 99%
“…42 Chen et al study found that common femoral was more commonly affected than the distal location (57.6% and 42.9%, respectively). 13 Peripheral arterial disease resulting from atherosclerosis is a multisegmental disease in approximately two-thirds of symptomatic patients. 16 In the study of Haltmayer et al, 25% of patients had stenoses and/or occlusions in 2 segments.…”
Section: Modalities To Localize the Lesions In Padmentioning
confidence: 99%
“…11,16 However, another clinical study showed that hypertension is significantly associated with proximal disease. 13 Smith study indicated that raised systolic blood pressure appears to be more strongly related to multisegment disease and that a raised diastolic pressure may predispose more to disease in the aortoiliac vessels. 7 Diehm et al found no relationship between hypertension and lesion sites.…”
Section: Factors That Contribute To the Distribution Of Padmentioning
confidence: 99%